Preparation of metal oxide thin films from organic-additive-free aqueous solutions by low-speed dip-coating1. Issue 26 (22nd March 2015) - Uchiyama, H.; Ito, T.; Sasaki, R.; Kozuka, H.
<x xml:space="preserve">Abstract</x> Transparent, crack-free SnO2 and TiO2 precursor films were obtained from organic-additive-free aqueous solutions by low-speed dip-coating. The precursor films were crystallized to SnO2 and TiO2 by the heat treatment at 700 °C for 10 min in air.